The incidence of personality disorders among substance dependents and non-addicted psychiatric clients - Zadeh, Majid Darvishi; Damavandi, Alireza Jilardi (Elsevier, 2010)
Resistance against treatment, severity of symptoms and relapse to substance addiction can be resulted from low attention and sometimes inattention to existence of personality disorders in substance dependent individuals in rehabilitation clinics. In order to study and compare the incidence of personality disorders in substance dependents and non-addicted psychiatric clients, Millon Clinical Multiaxial Inventory (MCMI) II was administered on 75 substance dependent males and 75 non-addicted psychiatric male clients. Age, gender, education level were controlled in both group of Clients.Findings show that the rate of personality disorder prevalence in substance dependent individuals was 45.3% in compare with 25.3% for the non addicted clients. Results of t-tests analyses indicate that the prevalence rate of personality disorders (specifically, borderline and anti-social personality disorders) in substance dependent individuals is significantly higher than this ratio in non-addicted psychiatric clients. Meanwhile, there was no significant difference between the two groups in narcissistic personality disorder. In conclusion, this study highlighted the importance of paying attention to personality disorders and their related treatments along with other approaches in treatment process of substance dependent individuals. Other implications are discussed.